2016
DOI: 10.14409/fa.v14i2.5716
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia De Fusariosis De La Espiga en Cultivares De Trigo Pan Durante 2012-13 en Marcos Juárez (Córdoba – Argentina).

Abstract: En 2012 se caracterizaron cultivares de trigo frente a ataques severos de Fusariosis de la espiga en Marcos Juárez en ensayos de RET y bajo infección artifi cial. Se determinó incidencia, severidad rendimiento de granos, peso de mil granos (PMG), peso hectolítrico (PH) , proporción de granos enfermos, contenido de deoxynivalenol (DON) y contenido de proteínas en granos, hallándose diferencias signifi cativas (p<0,05). Se afectó el PH, PMG y rendimiento. Presentaron baja infección Lenox, LE 2330, ACA 356, Klein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Recent reports indicated that bacterial diseases of cereals are increasing their incidence in recent years in Argentina and Uruguay (Terrile et al, 2019;Alberione, 2022;Martino et al, 2023). Several reports on leaf spots and discolorations not-associated to known fungal infections are found rather frequently in the elds worldwide, but they are associated to phytopathogenic bacteria (Butsenko et al, 2021;Rizzo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent reports indicated that bacterial diseases of cereals are increasing their incidence in recent years in Argentina and Uruguay (Terrile et al, 2019;Alberione, 2022;Martino et al, 2023). Several reports on leaf spots and discolorations not-associated to known fungal infections are found rather frequently in the elds worldwide, but they are associated to phytopathogenic bacteria (Butsenko et al, 2021;Rizzo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Out of the ve species, two of them, X. translucens pv. undulosa and P. syringae, are commonly pathogenic species isolated from wheat worldwide, and also in Argentina (Pozzi et al, 2023;Alberione, 2022); and for C. tessellarius, a recent report demonstrated that this species was responsible to cause bacterial mosaic on wheat in India (Nasiri et al, 2024), but no recent reports are found in Argentina; in the case of P. ananatis, and C. accumfaciens pv. accumfaciens, although their presence is sporadically reported in cereals, their impact as pathogenic species on wheat is still under study (Gonçalves, et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los resultados observados en la presente investigación fueron coincidentes con los de Alexander et al (1997), Chen et al (1995), Liu et al (1997) y Alberione et al (2015) donde tampoco se detectó correlación entre los niveles de infección y el contenido de micotoxinas. Mesterházy et al (1999) indican que la variabilidad se explica por la presencia de mecanismos de tolerancia que afectan la relación entre la severidad de la FET y la respuesta del rendimiento.…”
Section: Micotoxinasunclassified